Beberapa Faktor Yang Mempengaruhi Kepatuhan Pajak Wajib Pajak Badan Di Kota Makassar - Adzim, Faidul (Perpustakaan dan Penerbitan Unismuh Makassar, 2012)
This study aims (1) to know and analyze the influence of the attitude of the leadership of the company against taxpayer compliance bodies in the city of Makassar. (2) to know and analyze the influence of company's financial condition influence to taxpayer compliance agency in Makassar City. (3) to know and analyze the influence of corporate climate have an effect on taxpayer compliance in Makassar City. (4) to know and analyze the dominant factors influencing the taxpayer compliance of the agency in Makassar City. The instrument used for data collection is the next questionnaire data is processed and analyzed using multiple regression. The conclusion of this research are (1) tax compliance attitude have positive and significant effect to tax compliance for corporate taxpayer in Makassar City. The more positive the attitude of a corporate leader to tax compliance the higher the level of tax compliance agency. Conversely, the more negative the attitude of a company leader (in this case means not supporting) to tax compliance the lower the level of tax compliance. (2) The financial condition has a positive effect on Corporate Tax Compliance although not significant. The company's financial condition is good, then the Leader of the company will be obedient in carrying out the corporate taxation obligation which he represent or can be said high tax compliance level. These results reflect that the company's financial condition as reflected in the level of profitability and cash flow has proven to be one of the factors affecting the company's compliance with tax laws because profitability will pressure the company to report its taxes. (3) Organizational climate has a positive effect on Agency Tax Compliance significantly. A positive corporate organization climate will lead to high levels of tax compliance or vice versa. These results illustrate that a positive organizational climate will support corporate leaders to behave obediently. (4) Attitudes of tax compliance is the most dominant variable of influence on taxpayer compliance bodies in the city of Makassar. This indicates that the attitude of a positive corporate leadership in terms of understanding the rules and tax obligations will also behave positively in the reporting and payment of tax obligations.